Burden of Thyroid Cancer From 1990 to 2019 and Projections of Incidence and Mortality Until 2039 in China: Findings From Global Burden of Disease Study - Cheng, Fang; Xiao, Juan; Shao, Chunchun; Huang, Fengyan; Wang, Lihua; Ju, Yanli; Jia, Hongying (Frontiers in Endocrinology, 2021)
Abstract: Projecting the burden of thyroid cancer (TC) over time provides essential information to effectively plan measures for its management and prevention. Here, we obtained data from the Global Burden of Disease (GBD) Study between 1990 and 2019, to model how TC will affect China until 2039 by conducting the Bayesian age-period-cohort analysis. The number of new TC cases in China was 10,030 in 1990, 39,080 in 2019, and projected to be 47,820 in 2039. This corresponded to 3,320, 7,240, and 4,160 for deaths, respectively. And the disability-adjusted life years (DALYs) cases increased from 103,490 in 1990 to 187,320 in 2019. The age-standardized rate (ASR) of incidence increased from 1.01 to 2.05 during 1990-2019 and was projected to increase to 3.37 per 100,000 person-years until 2039. The ASR of mortality (ASMR) remained stable during study period and was projected to have a mild decline from 0.39 to 0.29/100,000 during 2020-2039. Although the ASMR in male has maintained an increasing trend in the past and will gradually decline with a speed of 1.07% per year after 2019. The most significant increase in crude incidence occurred in people aged 45-65 from 1990 to 2019, however will shift into young people aged 10-24 from 2020 to 2039. In addition, the proportion of deaths and DALYs caused by obesity increased from 1990 to 2019, and it affected men more than women. In conclusion, a substantial increase in counts of incidence of TC in China is projected over the next two decades, combined the slightly declined mortality, indicating that rational health policies are needed in the future to cope with the increase number of TC patients, especially among males and adolescents.